Evaluating Income-Based Performance Indicators in Oil Palm Smallholder Empowerment and Their Impact on Living Standards in Janja Village, Tolitoli Regency: Evaluasi Indikator Kinerja Berbasis Pendapatan dalam Pemberdayaan Petani Kelapa Sawit Skala Kecil dan Dampaknya terhadap Standar Hidup di Desa Janja, Kabupaten Tolitoli - Edi Yanto; Rahma Rahma (STIE MUJAHIDIN TOLITOLI, 2025)
This study aims to analyze the extent to which the empowerment of oil palm smallholders contributes to improving the standard of living of the community through increasing income in Janja Village, Lampasio District, Tolitoli Regency. Income is used as a key indicator of success because it reflects a household's economic ability to meet basic needs and improve quality of life. This study uses a qualitative approach with survey methods and interviews with 10 oil palm smallholder respondents with different land ownership specifications. The results of the study show that there is a need for empowerment programs for farmers both in terms of cultivation, crop management and the formation of farmer groups/cooperatives. Meanwhile, in terms of farmers' income, it was found that in a total of 30 hectares of land area from farmers produced 30.5 tons of oil palm production with an income value of Rp 50,650,000. This shows that there is an increase in income followed by farmers' land area. The larger the farmer's land is eating, the tendency of the farmer's income also increases. With the increase in income, the community has experienced improvements in the aspects of education, health, and housing. This study recommends the need for sustainability and capacity building of human resources in managing agricultural land, especially oil palm farming, sustainably.